Analisis Sistem Penganggaran Serta Pengaruhnya Terhadap Kinerja Keuangan Yayasan As-Syifa - Nurdiansyah, Dian Hakip (JURNAL ILMU MANAJEMEN DAN BISNIS, 2011)
Watchfulness aim that want achieved in this watchfulness (a) to detects and learn budgeting system in foundation assyifa al-khoeriyah, (b) to detect and learn finance performance in foundation assyifa al-khoeriyah, (c) to detect and learn budgeting system influence towards finance performance achievement in foundation assyifa al-khoeriyah. In this research uses descriptive and verification forms and methods of descriptive and explanatory survey. Data collection technique used was to analyze the financial reports as-Syifa foundation from 2005 until 2009. Methods of analysis and quantitative data using descriptive statistical analysis that uses path analysis (path analysis). The results of descriptive analysis showed that the planning and management control in the foundation asyifa good enough. The result of path analysis show the existence of linkages between the research variables, and the results of the estimated coefficients between variables influence the research can be determined that the planning and management control have an influence on the financial performance of As-Syifa foundation.Â